Predicting Solid–Liquid Equilibrium of Fatty Acid Methyl Ester and Monoglyceride Mixtures as Biodiesel Model Fuels. (12th July 2017) - Yoshidomi, Shinichiro; Sugami, Yuitsu; Minami, Eiji; Shisa, Noriko; Hayashi, Hitoshi; Saka, Shiro
Abstract: Fatty acid methyl esters from plant oils are the main component of biodiesel and used as a substitute for petroleum diesel. Biodiesel generally contains a small amount of monoglycerides as intermediate compounds, which have high melting points and often solidify and clog fuel filters. The prediction of the cold‐flow property of biodiesel is of great importance for practical application. In this study, a thermodynamic study was conducted for mixtures of monoglycerides and fatty acid methyl esters. Temperatures of the solid–liquid equilibrium for the mixtures were measured by differential scanning calorimetry and visual observation, while the theoretical values were calculated using the modified Universal Quasi‐chemical Functional‐group Activity Coefficients (UNIFAC) model (Dortmund). The theoretical and experimental results were in good agreement, especially for binary mixtures of monoglycerides and methyl esters. The importance of monoglycerides on the cold‐flow properties of biodiesel was determined, and the effects could be well described by the modified UNIFAC model (Dortmund).